Динаміка витрат та інвестицій у сфері поводження з відходами - Трофимчук, В.О. (Економіка природокористування і охорони довкілля, 2013)
Представлено результати статистичного аналізу особливостей економічної динаміки природоохоронних інвестицій. Доведено зв’язок динаміки цього виду інвестування із досягненням провідним технологічним укладом стадії зрілості або закінченням періоду індустріалізації / модернізації. In the article the results of the statistical analysis of the characteristics of economic dynamics of environmental investments. Increase environmental investments detects periodicity related to the medium-term economic cycles, periods of growth rates – with a cycle of economic modernization in the 1980s, and decline – the crisis of 2008–2009 brought us the dynamics of environmental investments while achieving a technological structure of maturity or expiration of the period of industrialization and modernization.